Democratic Television in The Netherlands - Slootweg, Tom; Aasman, Susan (VIEW Journal of European Television History and Culture, 2015)
For this article, the authors retrieved two curious cases of nonconformist TV from the archives of The Netherlands Institute of Sound and Vision. Being made in the late 1970s and early 1980s, the two cases represent an alternative history of broadcast television in the Netherlands. Whereas Neon (1979-1980) aimed to establish a punk-inspired DIY video culture, Ed van der Elsken (1980, 1981) strived for an expressive amateur film culture. The authors propose to regarded these cases as two different experiments of participation in and through media. By conceptualising amateur film and video as counter-technologies, the discursive expectations around their democratic potential can be explored further.